Characterization of Nano Silica prepared from Iraqi Rice Husk and its Application in Oil Well’s Cement - Saleh, Najat. J.; Abdulrahman, Amer. A.; Yousif, Zakia. A. (Journal of Petroleum Research and Studies, 2017)
Iraqi Rice husk (IRH) was used to produce nanosilica by precipitation method. The prepared silica nanoparticles samples were characterized using different analytical techniques, these included FTIR, XRD, SEM ,AFM and and,TEM. X-Ray fluorescence (XRF) was used for the quantitative determination of chemical composition of rice husk which revel that it contains 94.22% silica, after acid leaching it gave 99.04% silica. at 700 oC. FTIR showed bending and stretching absorption bands Si-O-Si at (797) cm-1, (1078) cm−1. X-Ray diffraction shows a strong broad characteristic peak of nano pure silica at ≈ 22°. Electron microscope image characterize particles size of (60) nm in spherical shape and agglomerated form. The observation by Atomic Force Microscope shows that the average diameter of particles 88.87 nm.The prepared nanosilica from rice husk has a surface area of(194m2/g) and pore volume of (0.275 cm3/g). Nanosilica pozzolanic material was used as cement admixture in oil field cement to improve compressive strength. The nanosilica cement admixture compressive strength was increase 8%, 9% and 4% at 1.5%, 2%, 2.5% nanosilica percentage adding respectively by weight of cement at 38 oC and 0.1%, 9%, 7% compressive strength percent increase at 60 oC. Keywords: Iraqi rice husk, Nanosilica, Oil well, cement-admixture.